Time spent looking at food during a delay of gratification task is positively associated with children's consumption at ad libitum laboratory meals. (1st October 2019) - Lundquist, Ella; Austen, Marielle; Bermudez, Maria; Rubin, Carter; Bruce, Amanda S.; Masterson, Travis D.; Keller, Kathleen L.
Abstract: Greater ability to delay gratification for an immediate food reward may protect against the development of obesity. However, it is not known if the behaviors children exhibit during a delay of gratification task are related to overeating in other contexts. The purpose of this analysis was to assess the relationship between observed child coping strategies during a delay of gratification task and laboratory intake from ad libitum test-meals. The sample consisted of 40, 7–9 year old children (40% (N = 16 with overweight/obesity). Across 5 laboratory visits, children consumed 3 identical test-meals presented after varying exposure conditions (i.e., no exposure, exposure to food commercials, exposure to toy commercials). On the first visit, children were recorded during a delay of gratification task which was coded for three behavioral themes: looking at vs. away from food, talking vs. staying silent, and fidgeting vs. sitting still. Pearson correlations and multiple regressions were run to look at the relationships between coping strategies and test-meal intake. Time spent looking away from food was negatively associated with ad libitum food consumption at the meals. Conversely, greater time spent looking at food was positively associated with ad libitum food consumption. These relationships were independent of covariates likely to influence intake (e.g., sex, age, weight status, parent income) and were more robust following food rather than toy commercial exposure. Children who spent more time looking at food and less time looking away during a delay of gratification task may be vulnerable to overeating in other contexts. Upon replication in larger samples, these behaviors could serve as modifiable targets in the development of childhood obesity prevention programs.